Effects of a brief web-based intervention on motivation, attitude, and physical activity in adults - Gasper, Rebecca L. (Kansas State University, 2018)
BACKGROUND: The high prevalence of physical inactivity in America is associated with the development of multiple chronic health conditions and a growing burden on the healthcare system, causing a public health crisis. An ineffective communication strategy regarding how and why people can be physically active may be partially to blame for this crisis. Messages coming from various sources, including physicians, the federal government, professional organizations, and the media, promote physical activity in a way that does not support the three key psychological needs of autonomy, competence, and relatedness described by the Self-Determination Theory (SDT). To address these deficiencies, the present study sought to compare the impact of brief online modules utilizing SDT-supportive strategies to promote autonomy and competence to information-based modules on participant levels of autonomous motivation, attitude, perceived behavioral control (PBC), and physical activity behavior. METHOD: Four online modules were developed for inactive adults ages 22-45 and were delivered over the course of four weeks via Qualtrics. Participants were randomized into the intervention (n=66) or control (n=66) condition, with the intervention modules including more autonomy-supportive content and recommendations to re-frame physical activity as a more feasible activity that one can benefit from immediately. Both groups completed modules relating to similar topics, including the benefits of physical activity, physical activity recommendations, barriers, and external influences. Repeated measures ANOVAs were utilized to examine changes in autonomous motivation, attitude, PBC, and physical activity behavior from pre-post intervention between groups. RESULTS: Participants from both groups reported an increase in autonomous motivation [F(1,66)=16.207, p=<.001], overall attitude towards physical activity [F(1,65)=4.726, p=.033], and PBC [F(1,66)=9.191, p=.002]. There was no significant change in physical activity behavior [F(1,68)=.122, p=.728] during the four-week pre-post assessment, and there were no significant differences detected between groups. CONCLUSION: A four-week online intervention positively impacted autonomous motivation, attitude, and perceived behavioral control regarding individual physical activity behavior. These findings suggest that implementing recommendations to re-frame physical activity through brief interactive and information-based modules could be an effective strategy to increase the psychological precursors of physical activity behavior. However, additional strategies may be necessary to translate psychological changes to physical activity behavior. Future interventions could benefit from identifying ways to increase the reach of the program and incorporating a longer follow-up to assess if the psychological changes are translated to behavior.
Keywords: Physical activity; Self-Determination Theory; Web-based interventionMotivation